Evolution of Scientific Concepts About the Role of Investments in the Economy (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article is devoted to the history of revealing the essence of the category “investment” in the works of the classics of economic theory, which is a necessary condition for correctly considering the essence of investment as the main factor in ensuring the breakthrough economic development of the country.